2022
DOI: 10.1186/s13045-021-01219-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neutralisation of SARS-CoV-2 delta variant in vaccinated patients with B cell chronic lymphocytic leukaemia

Abstract: Background Immune suppression is a clinical feature of chronic lymphocytic leukaemia (CLL), and patients show increased vulnerability to SARS-CoV-2 infection and suboptimal antibody responses. Method We studied antibody responses in 500 patients following dual COVID-19 vaccination to assess the magnitude, correlates of response, stability and functional activity of the spike-specific antibody response with two different vaccine platforms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…In multivariate analysis, seroconversion was more frequently observed in patients ≤ 65 years old, in females, in patients not on active therapy and in patients with IgG levels > 550 mg/dL. Parry et al observed a markedly negative impact of receiving Bruton tyrosine kinase inhibitor or anti-CD20 therapy within the year before vaccination on serological response rates to SARS-CoV-2 mRNA (BNT162b2, n=204) or adenoviral (ChAdOx1 nCov-19, n=296) vaccine in a large cohort of 500 patients (median age 67 years) with CLL in which 67% of the patients acquired anti-spike IgG (versus 100% in healthy controls) (99). Importantly, CLL patients with a serological response had markedly lower neutralizing Ab against the Delta SARS-CoV-2 variant than healthy controls.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…In multivariate analysis, seroconversion was more frequently observed in patients ≤ 65 years old, in females, in patients not on active therapy and in patients with IgG levels > 550 mg/dL. Parry et al observed a markedly negative impact of receiving Bruton tyrosine kinase inhibitor or anti-CD20 therapy within the year before vaccination on serological response rates to SARS-CoV-2 mRNA (BNT162b2, n=204) or adenoviral (ChAdOx1 nCov-19, n=296) vaccine in a large cohort of 500 patients (median age 67 years) with CLL in which 67% of the patients acquired anti-spike IgG (versus 100% in healthy controls) (99). Importantly, CLL patients with a serological response had markedly lower neutralizing Ab against the Delta SARS-CoV-2 variant than healthy controls.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“… 42 A single subcutaneous dose of casirivimab and imdevimab (REGEN‐COV), a combination of the monoclonal antibodies casirivimab and imdevimab, was shown to prevent symptomatic infection throughout a 28‐day period. 42 Thus, REGEN‐COV could potentially be used for long‐term prophylaxis in individuals at risk for SARS‐CoV‐2 infection who only have limited benefit from vaccination, including patients with CLL. This combination therapy retains neutralization potency against circulating SARS‐CoV‐2 variants of concern, including B.1.1.7 (Alpha), B.1.351 (Beta), B.1.617.2 (Delta), B.1.429 (Epsilon), and p .1 (Gamma), both in vitro and in vivo, and may well protect against a selection of resistant variants.…”
Section: The Management Of Patients With Molecular Variants: Beyond T...mentioning
confidence: 99%
“…This combination therapy retains neutralization potency against circulating SARS‐CoV‐2 variants of concern, including B.1.1.7 (Alpha), B.1.351 (Beta), B.1.617.2 (Delta), B.1.429 (Epsilon), and p .1 (Gamma), both in vitro and in vivo, and may well protect against a selection of resistant variants. 42 , 43 However, this monoclonal antibody is not currently an option for many patients due to the striking prevalence l of the Omicron variant worldwide. REGEN‐COV is indeed inactive against Omicron variants and should only be used in patients with proven infection with other strains of the virus (e.g., Delta variant).…”
Section: The Management Of Patients With Molecular Variants: Beyond T...mentioning
confidence: 99%
“…Focusing on cancer patients and patients with autoimmune diseases, there are several studies that showed impaired antibody responses following dual COVID-19 vaccination in patients with chronic lymphocytic leukemia ( 81 ) and lung cancer ( 82 ). Furthermore, it was proved that humoral protection against the delta variant is markedly impaired among chronic lymphocytic leukemia patients, indicating the urgent need for further optimization of immune protection in this patient cohort ( 81 ). Yet, not enough data were reported about the status humoral protection for patients with autoimmune diseases.…”
Section: Methodsmentioning
confidence: 99%